Transition-Metal-Free Efficient Synthesis of Bisindole Sulfanes Using 2-(Fluorosulfonyl)difluoroacetic Acid - Li, Yang; Shi, Lan-Ting; Zhu, Wen-Qing; Li, Hong; Zhang, Qiang (Synlett, 2018)
By using 2-(fluorosulfonyl)difluoroacetic acid as sulfur reagent, bisindole sulfanes were highly efficient synthesized under transition-metal-free conditions. Results indicate that this proceeded not at the relatively acidic C-2 position but rather selectively at the nucleophilic C-3 position to give the desired compounds with excellent regioselectivities and good yields.
Keywords: synthesis; indoles; 2-(fluorosulfonyl)difluoroacetic acid; sulfur reagent; bisindole sulfanes